Microsatellite variation between an African and five European taurine breeds results in a geographical phylogenetic tree with a bison outgroup - Mommens, G.; Peelman, L.J.; Zeveren, A. van; D'Ieteren, G.D.M.; Wissocq, N.M. (Wiley, 1999)
The genetic relationship between five Belgian breeds (Belgian Blue, Black Pied, Red Pied, White and Red of East Flanders, Red of West Flanders), an African taurine N'Dama breed and a captive American bison herd was studied by means of 31 microsatellite loci. On the basis of the allele frequencies of the 31 scored loci, Nei's modified genetic distance was calculated between the populations. The neighbour joining clustering algorithm was used to construct a possible phylogenetic tree. Herein American bison served as an outgrouThe dendrogram displays a geographical topology with three major lineages as expected, but is unclear in clustering the local breeds.